Gaya Kepemimpinan Situasional Pimpinan Sekolah SDIT Ash-Shofa dalam Meningkatkan Kinerja Guru - Sekar Ayu Widiastuti; Hingggil Permana (Departement of Mathematics Education, 2023)
The success of a school institution is determined by many factors, one of which is leadership by the principal. The principal is given the task of being responsible for managing, driving the school optimally in order to achieve the goals and vision and mission of the school. In order to achieve the goal of course the principal must have the ability to be an example for his subordinates. The principal as a leader must provide and show his leadership properly, one of which is by arriving on time and carrying out his duties in accordance with his duties and functions to motivate his subordinates, by doing this indirectly encourages and motivates teacher performance to have skills. The main focus in my research is situational leadership carried out by the principal of SDIT Ash-Shofa. The purpose of this study is to explain objectively how the leadership of a woman in Islam can influence decision making in the institutions she leads. The method used in this research is observation.